A new species of Janusius Bretfeld, 2010 (Collembola, Sminthuridae) from the Korean Peninsula, with a key to the species of the genus - Dányi, László; Park, Kyung-Hwa (Zootaxa, 2016)
Janusius geumgangensis sp. nov. is described and illustrated based on specimens from North Korea. The new species is characterised by having 3 spatulate chaetae on all tibiotarsus, 4 chaetae on retinaculum, smooth anal appendage, anterior chaetotaxy of dens 3,3,3,2,2,1,1, colouration with one pair brownish lateral spot and presence of mucronal chaeta. The genus Janusius Bretfeld, 2010 is first mentioned from the Korean Peninsula, although another species described from there as Sminthurus annulatus Kang & Lee, 2005 is recognised here as belonging to this genus (Janusius annulatus (Kang & Lee, 2005) comb. nov.), too. A key including all known species of the genus is presented as well.